Suboptimal vitamin B intakes of Zambian preschool children: Evaluation of 24-hour dietary recalls - Titcomb, Tyler J.; Schmaelzle, Samantha T.; Nuss, Emily T.; Gregory, Jesse F.; Tanumihardjo, Sherry A. (SAGE Publications, 2018)
Hidden hunger affects individuals who chronically consume an inadequate intake of at least 1 micronutrient and is associated with low dietary diversity. Little data are available on dietary intake or status assessment of B vitamins among preschool children in Zambia.The aim of this study was to assess 24-hour dietary recall records obtained from Zambian children aged 3 to 7 years for B vitamin intake in relation to adequacy and change over time in the same community.Twenty-four-hour dietary recalls were collected from 2 studies that were 2 years apart in the same district of Zambia. Data were retrospectively analyzed for B vitamin intake, that is, biotin, vitamin B12, folate, niacin, pantothenic acid, vitamin B6, riboflavin, and thiamin. The estimated average requirement (EAR) cut point method was used to assess inadequacy prevalence for EARs established by the Institute of Medicine in the United States.For all B vitamins, mean values were below the EARs established for children 4 to 8 years old. Relative to the EAR, children had the highest intakes of vitamin B6 with inadequacies of 77.9% and 60.1% in 2010 and 2012, respectively. The highest prevalence of inadequate intake was associated with folate, where ≥95% of the children had intakes below the EAR in both studies.All median vitamin B intakes were inadequate among these young children in rural Zambia. Future researchers and policy makers may need to consider B vitamin status in resource-poor areas of the country.